2004
DOI: 10.1029/2004gl020425
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional flushing times of the Persian Gulf

Abstract: [1] A three-dimensional hydrodynamic model is employed in a fully prognostic mode to derive flushing times of the Persian Gulf-an evaporation-driven inverse estuary that is governed by import of surface water from the adjacent ocean and export of saline bottom gulf water through the Strait of Hormuz. During spring and summer, a cyclonic overturning circulation establishes along the full length of the Gulf. During autumn and winter, this circulation breaks up into mesoscale eddies, laterally stirring most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Significant amounts of fine-mode aerosols produced by the petroleum industry and related shipping activities are observed (Basart et al, +2.74 ± 1.78 % yr −1 for MISR-Terra, +1.72 ± 1.13 % yr −1 for SeaWiFS-OrbView-2 AOT, and +3.84 ± 2.66 % yr −1 for MODIS-Aqua). This has been explained by increases of coarse-mode aerosols from deserts (+3.37 % yr −1 for coarse-mode dominant AOT from 2001 to 2007 at the Solar_Village station, Yoon et al, 2012) and fine-mode aerosols from oil production, refining, and other industry in and around the Red Sea and the Persian Gulf (Sadrinasab and Kämpf, 2004). The increasing trends are comparable to the results; +0.0092 ± 0.0026 yr −1 from 1997 to 2010 over the Arabian Peninsula (Hsu et al, 2012) Aerosol over the Indian subcontinent, as shown in region 4 in Fig.…”
Section: Trend Validation With Aeronet Observationmentioning
confidence: 99%
“…Significant amounts of fine-mode aerosols produced by the petroleum industry and related shipping activities are observed (Basart et al, +2.74 ± 1.78 % yr −1 for MISR-Terra, +1.72 ± 1.13 % yr −1 for SeaWiFS-OrbView-2 AOT, and +3.84 ± 2.66 % yr −1 for MODIS-Aqua). This has been explained by increases of coarse-mode aerosols from deserts (+3.37 % yr −1 for coarse-mode dominant AOT from 2001 to 2007 at the Solar_Village station, Yoon et al, 2012) and fine-mode aerosols from oil production, refining, and other industry in and around the Red Sea and the Persian Gulf (Sadrinasab and Kämpf, 2004). The increasing trends are comparable to the results; +0.0092 ± 0.0026 yr −1 from 1997 to 2010 over the Arabian Peninsula (Hsu et al, 2012) Aerosol over the Indian subcontinent, as shown in region 4 in Fig.…”
Section: Trend Validation With Aeronet Observationmentioning
confidence: 99%
“…In water bodies that are as shallow as the Gulf, the water mixed layer and atmospheric mixed layer are of comparable heat content, and the two components of a coupled system evolve simultaneously with significant two-way interactions. Previous regional modeling studies either used specified surface fluxes to simulate the hydrodynamics of the Gulf (Chao et al 1992; Kämpf and Sadrinasab 2006;Sadrinasab and Kämpf 2004;Thoppil and Hogan 2010;Yao and Johns 2010a;Yao and Johns 2010b;Hassanzadeh et al 2011;Hassanzadeh et al 2012) or prescribed SST in simulating the regional atmospheric climate (Evans et al 2004;Marcella andEltahir 2008, 2012). Because of the shallow nature of this water body, neither of these two approaches is suitable for addressing the above questions or projecting future climate in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Circulation and water mass formation in the Persian Gulf have been the subject of several previous modeling studies (Lardner et al, 1993;Chao et al, 1992;Blain, 2000;Sadrinasab and Kämpf, 2004;Kämpf and Sadrinasab, 2006;Azam et al, 2006). Several of these studies used hydrodynamic numerical models or spectral models of coarse to moderate horizontal resolutions (20-5 km), and were driven by monthly mean density or atmospheric forcing.…”
Section: Introductionmentioning
confidence: 99%